2018
DOI: 10.1016/j.arcontrol.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Control of connected and automated vehicles: State of the art and future challenges

Abstract: Autonomous driving technology pledges safety, convenience, and energy efficiency. Challenges include the unknown intentions of other road users: communication between vehicles and with the road infrastructure is a possible approach to enhance awareness and enable cooperation. Connected and automated vehicles (CAVs) have the potential to disrupt mobility, extending what is possible with driving automation and connectivity alone. Applications include real-time control and planning with increased awareness, routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
260
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(286 citation statements)
references
References 211 publications
0
260
0
2
Order By: Relevance
“…A detailed discussion of the research efforts that have been reported in the literature to date in this area can be found in [28] and [37].…”
Section: A Related Workmentioning
confidence: 99%
“…A detailed discussion of the research efforts that have been reported in the literature to date in this area can be found in [28] and [37].…”
Section: A Related Workmentioning
confidence: 99%
“…For the eco-routing case, we only show the results for solving (4). In other words, we only solve the eco-routing problem for conventional vehicles using the energy model discussed in Section III-A.…”
Section: Non-cav Flow Modelingmentioning
confidence: 99%
“…Lately, a decentralized optimal control framework was presented for coordinating online CAVs in different transportation scenarios, yet without considering state and control constraints; see Ntousakis et al (2016); Zhao et al (2019), or without considering rear-end collision avoidance constraint; see Malikopoulos et al (2018). A detailed discussion of the research efforts in this area can be found in recent survey papers (Rios-Torres and Malikopoulos, 2017;Guanetti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%